OBESITY IN CHILDREN – EPIDEMIOLOGY, CAUSES, AND HEALTH CONSEQUENCES - A LITERATURE REVIEW - Mateusz Cieciora; Małgorzata Kawiorska; Julia Surowiec; Ilona Mariańska-Wiśniewska; Angelika Szwaj; Aleksandra Cieciora; Aleksandra Simlat; Tomasz Puszkiel; Adrianna Świerzyńska; Natalia Jankowska (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Childhood obesity is one of the most serious challenges facing public health today. Its prevalence is steadily increasing worldwide, affecting both developed and developing countries. This disease is chronic, progressive, and multifactorial. Its development is the result of complex interactions between genetic, environmental, behavioral, psychosocial, and neurohormonal factors. The main causes include poor eating habits, low levels of physical activity, a sedentary lifestyle, socioeconomic factors, and the influence of the family environment. Obesity that develops in childhood often persists into adulthood, leading to a significantly increased risk of premature onset of chronic diseases, reduced quality of life, and shortened life expectancy. Aim of the study: The aim of this study was to present a comprehensive review of the problem of obesity in children and adolescents by analyzing current epidemiological data, etiology, health complications, and contemporary treatment strategies. Material and methods: This paper is a review of the literature covering current experimental, observational, and randomized controlled trials on childhood obesity. Data on the prevalence of the disease, risk factors, metabolic, cardiovascular, bone and psychosocial disorders, as well as the effectiveness of non-pharmacological interventions, pharmacotherapy and surgical treatment were analyzed. Results and conclusions: A review of the literature indicates that the prevalence of obesity among children and adolescents is steadily increasing, posing a significant clinical and social problem. Childhood obesity is associated with an increased risk of developing insulin resistance, type 2 diabetes, dyslipidemia, hypertension, and premature atherosclerotic changes, which can lead to cardiovascular disease in adulthood. Excessive body weight also negatively affects the musculoskeletal system and is associated with psychosocial consequences such as low self-esteem, anxiety, and depression. Effective treatment requires early diagnosis and an individually tailored, interdisciplinary approach based primarily on lifestyle modification, including healthy eating habits, increased physical activity, and behavioral interventions involving the whole family. Long-term and comprehensive therapeutic management is crucial to reducing the risk of complications later in life.